Integration of regulatory networks by NKX3-1 promotes androgen-dependent prostate cancer survival - Tan, Peck Yean (2013)
The NKX3-1 gene is a homeobox gene required for prostate tumor progression, but how it functions is unclear. Here, using chromatin immunoprecipitation coupled to massively parallel sequencing (ChIP-seq) we showed that NKX3-1 colocalizes with the androgen receptor (AR) across the prostate cancer genome. We uncovered two distinct mechanisms by which NKX3-1 controls the AR transcriptional network in prostate cancer. First, NKX3-1 and AR directly regulate each other in a feed-forward regulatory loop. Second, NKX3-1 collaborates with AR and FoxA1 to mediate genes in advanced and recurrent prostate carcinoma. NKX3-1- and AR-coregulated genes include those found in the “protein trafficking” process, which integrates oncogenic signaling pathways. Moreover, we demonstrate that NKX3-1, AR, and FoxA1 promote prostate cancer cell survival by directly upregulating RAB3B, a member of the RAB GTPase family. Finally, we show that RAB3B is overexpressed in prostate cancer patients, suggesting that RAB3B together with AR, FoxA1, and NKX3-1 are important regulators of prostate cancer progression. Collectively, our work highlights a novel hierarchical transcriptional regulatory network between NKX3-1, AR, and the RAB GTPase signaling pathway that is critical for the genetic-molecular-phenotypic paradigm in androgen-dependent prostate cancer.